Impacts of Covid-19 Pandemic on Global Agriculture, Livelihoods and Food Systems - Aravind Jayaraman; Burhan Özkan; Surendran Arumugam; Prahadeeswaran Mockaısamy (Journal of Agricultural Sciences)
The COVID-19 pandemic is brutally hitting many countries in the world. Immense consequences on food, health, and livelihoods are dreaded. The agricultural sector is a crucial part of the developing economy and provides livelihood to a large section of the people. Therefore, the disruption in agriculture and food systems will have significant impacts. This paper performs an inclusive assessment of the effect of COVID-19 on agriculture and food systems in the major part of the countries. A detailed discussion on reports, scientific publications, press releases, and organizational statements are reviewed. This review addresses and highlights COVID- 19 direct impacts in the food systems, market access for agricultural commodities, food and nutritional security, labour availability and migration, farm systems restore, inputs and outputs integration, the importance of IT in agriculture and lesson learning from these effects. In addition, this paper suggests coping and mitigation mechanisms that could be useful to improve and sustain livelihoods. Furthermore, this collective review is helpful to investigators, Government organizations, agricultural departments, and policymakers to expedite an effective response against the Covid-19 pandemic.